Cathartidae Lafresnaye 1839 - Somenzari, Marina; Amaral, Priscilla Prudente do; Cueto, Víctor R.; Guaraldo, André de Camargo; Jahn, Alex E.; Lima, Diego Mendes; Lima, Pedro Cerqueira; Lugarini, Camile; Machado, Caio Graco; Martinez, Jaime; Nascimento, João Luiz Xavier do; Pacheco, José Fernando; et al. (Zenodo, 2018)
Cathartidae [ Vultur gryphus ] (VAG): occurs in the Andes from Venezuela to Tierra del Fuego, and at sea level in Peru and Chile (Houston, 1994). In Brazil, there are only two old, occasional and undocumented records: on the Jauru River/ Mato Grosso (MT) and western PR (Sick, 1997). : Published as part of Somenzari, Marina, Amaral, Priscilla Prudente do, Cueto, Víctor R., Guaraldo, André de Camargo, Jahn, Alex E., Lima, Diego Mendes, Lima, Pedro Cerqueira, Lugarini, Camile, Machado, Caio Graco, Martinez, Jaime, Nascimento, João Luiz Xavier do, Pacheco, José Fernando, Paludo, Danielle, Prestes, Nêmora Pauletti, Serafini, Patrícia Pereira, Silveira, Luís Fábio, Sousa, Antônio Emanuel Barreto Alves de, Sousa, Nathália Alves de, Souza, Manuella Andrade de, Telino-Júnior, Wallace Rodrigues & Whitney, Bret Myers, 2018, An overview of migratory birds in Brazil, pp. 1-66 in Papéis Avulsos de Zoologia 58 on page 38, DOI: 10.11606/1807-0205/2018.58.03, http://zenodo.org/record/5234679 : {"references": ["Houston, D. 1994. Vultur gryphus. In: del Hoyo, J.; Elliott, A. & Sargatal, J. Handbook of the birds of the world, Vol. 2: New World Vultures to Guineafowl. Barcelona, Lynx Edicions. p. 40.", "Sick, H. 1997. Ornitologia brasileira. Edicao revista e ampliada. Rio de Janeiro, Nova Fronteira."]}